Cidadania e saúde no lugar: concepções de formadores de opinião na fronteira internacional entre Brasil, Paraguai e Argentina - Arenhart, Carlos Guilherme Meister (2020)
The international frontier territories were excluded from effective longitudinal actions in the scope of health management, policy and planning. Some specific projects were implemented in shortterm periods, without major repercussions on the organization, the flow of care and access to municipal health care networks. In the case of Foz do Iguaçu, in addition to the territorial complexity - being on a triple frontier - the immense population and cultural diversity, selective primary care and great dilution of health equipment throughout the territory, in addition to health surveillance with fragmented characteristics. These variables hinder an effective debate around the right to health and the exercise of citizenship in a border region. Thus, it was defined as a research question: How do opinion makers in the tri-national border region between Brazil, Paraguay and Argentina understand and represent the category of citizenship and the right to health in this territory? The research, with a qualitative approach, had the general objective of identifying how the category of citizenship and the right to health are expressed in the international border territory between Brazil, Paraguay and Argentina. And as specific objectives: (1) Analyze the understanding of opinion makers who live in the area, about citizenship and the right to health in the triple border region between Brazil, Argentina and Paraguay; (2) Identify possible consequences resulting from a restricted notion of citizenship in this place and (3) Point out strategies for facing barriers in order to fully exercise the right to health at the border. In order to realize these objectives, in-depth interviews were conducted with opinion makers (journalists, public health workers, social movement leaders and university professors). The interviews were conducted from September to December 2019, lasting approximately 40 minutes. After the transcription, the narratives were systematized into thematic nuclei, with the emergence of six nuclei: (1) “The subject and his sense of citizenship in a historical context at the trinational border”, (2) “The subject and his sense of citizenship in an empirical context in the city de Foz do Iguaçu ", (3)" The subject and his sense of citizenship in a social context in the cross-border territory ", (4)" The right to health in the border territory: multiple social representations ", (5)" The (un) knowledge and dialectic on legislation and access to health for cross-border citizens ”; and (6) “Overcoming obstacles: possibilities and discursive contradictions”. The results were presented in two articles that make up this dissertation, using dialectical hermeneutics and the Social Representations Theory as theoretical references. The results indicate that citizenship rights are not guaranteed to all citizens in the tri-national territory, with hierarchical relations of citizenship and a diversity of understandings regarding the management of citizenship in this territoriality. It is concluded that the understanding of the border as a space of integration and not of division can break with the axiomatic idea of sub-citizenship, strengthening humanitarian and solidarity ties between border societies.